PENGHARGAAN PROFESI GURU SEBAGAI AGEN PERUBAHAN - Marjuni, Andi (Inspiratif Pendidikan, 2020)
Appreciation for the success of teachers as agents of change is an extraordinary form of motivation for teachers. The competitive climate in the environment for teachers will be even more motivated. All teachers have expectations and compete for awards as outstanding and quality teachers in order to improve the professionalism of their duties. Apart from appreciation in a profession, it is no less important, namely protection in carrying out obligations both legally and in other ways. Protection greatly affects the productive performance of a teacher. Efforts to educate the nation’s life are the responsibility of education, especially in preparing students to become subjects who fear God Almighty, have a noble character, are tough, creative, independent, democratic, and professional in their respective fields.